PATHWAYS TO NET ZERO: CASE STUDIES FROM THAILAND ON THE ROLE OF SMART TECHNOLOGIES IN URBAN PLANNING - Rana, Shreema; Pokharel , Rojina (Tata Kota dan Daerah, 2025)
This paper explores the pivotal role of smart technologies in advancing net zero emissions within urban environments. With cities as major contributors to global carbon emissions, incorporating smart technologies into urban sustainability emerges as a critical strategy. This study employs a qualitative literature review to investigate how smart technologies contribute to net zero emissions in urban planning, focusing on smart infrastructure, environmental monitoring, and traffic management, with case studies carried out in emerging smart cities in Southeast Asia, namely Bangkok, Chiang Mai, and Phuket, illustrating practical applications. The study acknowledges potential biases, including regional focus and publication bias, that may impact the generalizability of the findings. The findings demonstrate that smart infrastructure significantly lowers energy consumption. Environmental monitoring provides actionable insights into air quality and pollutant levels, enabling targeted interventions, while intelligent traffic management systems reduce congestion and optimize transportation networks, significantly lowering vehicular emissions. The results underscore the effectiveness of these smart technologies in achieving net zero emissions, highlighting their potential to reshape urban landscapes into sustainable, low-carbon environments. The paper concludes by addressing the broader implications for urban planning and policy-making while promoting integrated approaches that align with net zero goals, offering a strategic roadmap for cities to implement smart technologies in their sustainability efforts.